Effects Of Peeling And Calamansi (Citrofortunella Microcarpa) Juice Addition On The Quality Parameter Of Fresh And Pasteurized Sugarcane (Saccharum Officinarum) Juice - Noor, Noor Afiqah Md (2020)
Fresh sugarcane juice is popular in Malaysia. However, it is susceptible to chemical changes and microbial spoilage that occur due to oxidation and contamination. Marketability of sugarcane juice is limited due to the unattractive dark colour caused by chemical changes. This study was conducted to determine the effects of peeling and calamansi juice addition on the quality parameters of fresh and pasteurized sugarcane juice. First part of the study was conducted to investigate the microbiological count of fresh sugarcane juice obtained from vendors located in Penang. The total plate count (TPC) of sugarcane juice obtained from vendors ranged from 4.89-7.40 Log CFU/mL, total coliforms (TC) of 38-1100 MPN/mL and faecal coliform (FC) of 3-75 MPN/mL. Result showed that TPC, TC and FC of sugarcane juice that was peeled before pressing was lower than unpeeled sugarcane juice. The second and third part were carried out to determine the effects of peeling and calamansi juice addition (1.0%, 1.5% and 3.0%) on the physicochemical, antioxidant, and microbiological properties of fresh and pasteurized (70ºC for 10 minutes) sugarcane juice respectively. Sugarcane peel consists of polyphenolic compounds such as anthocyanin that contribute to colour and antioxidant of juice. Therefore, fresh and pasteurized sugarcane juice pressed without its peel produced significantly (P<0.05) higher Lightness (L*) value but lower antioxidant properties. Fresh sugarcane juice pressed without its peel showed significantly (P<0.05) lower microbial count compared to sugarcane juice pressed with its peel.